Історичний розвиток, сучасний стан та проблема відродження старовинних парків Правобережного Лісостепу України - Klimenko, Y.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 1999)
The short description of the ancient parks of the Vinnitsa, Zhitomir (forest-steppe part), Kyiv, Cherkasy regions is given. Three levels of degradation (landscape, taxonomic, phytocenotic) are shown and propositions on their restoration are offered.